The Effects of Spaced Practice on Second Language Learning: A Meta‐Analysis. Issue 1 (6th February 2022) - Kim, Su Kyung; Webb, Stuart
Abstract: This meta‐analysis investigates earlier studies of spaced practice in second language learning. We retrieved 98 effect sizes from 48 experiments ( N = 3, 411). We compared the effects of three aspects of spacing (spaced vs. massed, longer vs. shorter spacing, and equal vs. expanding spacing) on immediate and delayed posttests to calculate mean effect sizes. We also examined the extent to which nine empirically motivated variables moderated the effects of spaced practice. Results showed that (a) spacing had a medium‐to‐large effect on second language learning; (b) shorter spacing was as effective as longer spacing in immediate posttests but was less effective in delayed posttests than longer spacing; (c) equal and expanding spacing were statistically equivalent; and (d) variability in spacing effect size across studies was explained methodologically by the learning target, number of sessions, type of practice, activity type, feedback timing, and retention interval. The methodological and pedagogical significance of the findings are discussed. Abstract :